MECHANISMS FOR THE DEVELOPMENT OF UPPER-CLASS ENGLISH LEARNERS BY MIMICKING LISTENING COMPREHENSION SKILLS. - Odilova Shoira Odiljon qizi, (TADQIQOTLAR.UZ, 2024)
Annotatsiya. This article explores the mechanisms by which upper-class English learners can enhance their listening comprehension skills through mimicry. Listening comprehension is crucial for language acquisition, enabling learners to understand and interact effectively in the target language. This study reviews existing literature on the topic, presents methods for implementing mimicry in language learning, and analyzes the results of various approaches. The findings highlight the effectiveness of mimicry in improving listening skills and offer practical suggestions for language educators and learners.